1996
DOI: 10.1046/j.1464-410x.1996.08524.x
|View full text |Cite
|
Sign up to set email alerts
|

The day‐to‐day variation (test‐retest reliability) of residual urine measurement

Abstract: Although the PVR determined by TAUS may be useful to indicate aspects of bladder dysfunction or outlet obstruction, the wide variation in repeated measurements in the same individual limits its use for any clinical purpose that requires repeated assessment, e.g. in monitoring the response to treatment. There is poor test-retest reliability and PVRs cannot be determined reliably from a single measurement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
33
1
2

Year Published

1998
1998
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(38 citation statements)
references
References 0 publications
2
33
1
2
Order By: Relevance
“…[9][10][11]20 In addition, the present study showed that baseline PVR was a significant static variable to predict treatment failure. Although it is known that PVR is not an appropriate objective parameter, because its value fluctuates with each evaluation 23 and baseline PVR has little prognostic value for the risk of BPH-related invasive therapy in patients on a1-blockers and watchful waiting, 24 it is reported that the treatment failure rate was significantly high for patients with PVR Ն30 mL as well as those with a PV Ն35 mL, a history of AUR or complications of overactive bladder symptoms. 14 The present study had several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…[9][10][11]20 In addition, the present study showed that baseline PVR was a significant static variable to predict treatment failure. Although it is known that PVR is not an appropriate objective parameter, because its value fluctuates with each evaluation 23 and baseline PVR has little prognostic value for the risk of BPH-related invasive therapy in patients on a1-blockers and watchful waiting, 24 it is reported that the treatment failure rate was significantly high for patients with PVR Ն30 mL as well as those with a PV Ն35 mL, a history of AUR or complications of overactive bladder symptoms. 14 The present study had several limitations.…”
Section: Discussionmentioning
confidence: 99%
“…For simplicity, correlation coeBcient of only −0.19 (-0.22 in the study by Barry et al [7]). There was no significant association between the symptom of feeling of incomplete bladder variation in Q max measured on either the same or diCerent days, and Dunsmuir et al [14] have shown poor test-retest reliability for the measurement of PVR. Thus, studies be discarded, with a diagnosis being based on symptoms alone, or can the data from low volume voids while LUTS are important in that they are what bother patients, their significance in terms of reflecting a demonbe used to make a diagnosis?…”
mentioning
confidence: 85%
“…Estudios reportan que el VP no se correlaciona con la intensidad de los síntomas, pero sí parece existir asociación con el flujo máximo (1). Un estudio ha encontrado que el ángulo uretroprostático y el grado de protrusión intravesical prostática si estarían relacionados con la severidad de la obstrucción (15).…”
Section: Discussionunclassified